The Influence of Foundational Bases of Internet-Only Banks on Consumer Attitudes and Usage Intentions: Focused on the Moderating Effect of Involvement, Usage Purpose, and Construal Level - Kim, Ai-Young; Kim, Gwi-Gon (Journal of Ecohumanism, 2024)
This study investigates how the foundational bases of internet-only banks shape consumer attitudes and intentions to use these services. Specifically, it examines how consumer attitudes and usage intentions toward internet-only banks are moderated by factors such as involvement, purpose of use, and construal level. This research contrasts consumer attitudes based on the foundational bases of internet-only banks (ICT-driven vs. bank-driven) and analyzes whether involvement (high vs. low) and usage purpose (deposit vs. loan) have moderating effects on these attitudes. Furthermore, it explores whether construal level (low vs. high) moderates usage intentions depending on the bank’s foundational base (ICT-driven vs. bank-driven). For empirical analysis, two types of surveys representing ICT-driven and bank-driven internet-only banks were administered to a sample of 360 participants, including university students, graduate students, and the general public in Daegu and Gyeongbuk. Key Findings: 1) Consumer attitudes were significantly more favorable toward ICT-driven internet-only banks compared to bank-driven counterparts. 2) High involvement correlated with more positive attitudes toward ICT-driven internet-only banks, whereas low involvement correlated with more favorable attitudes toward bank-driven banks. 3) For usage purpose, consumers with a loan-oriented purpose demonstrated a stronger positive attitude toward ICT-driven internet-only banks, while, counter to the hypothesis, deposit-oriented consumers also showed a preference for ICT-driven banks. 4) Regarding construal level, lower construal levels were associated with stronger usage intentions for ICT-driven internet-only banks. Unexpectedly, high construal levels also displayed elevated usage intentions for ICT-driven models. In conclusion, initial consumer responses to internet-only banks, which incorporate ICT as an enabling technology within essential financial services, appear to prioritize convenience and procedural efficiency. This study thus offers theoretical insights suggesting that both internet-only and traditional banks should address these consumer demands by enhancing service speed and simplicity.